The Effect of Ratio Forage and Concentrate on The Dry Matter Consumption, Dry Matter and Organic Matter Digestibility in Etawa Crossbreed Dairy Goats - Akbar, Khoirul; Wanniatie, Veronica; Liman, Liman; Muhtarudin, Muhtarudin (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This study aims to determine the effect of ratio forage and concentrate on the dry matter consumption, dry matter and dry organic matter digestibility in etawa crossbreed dairy goats. This research was conducted in November-December 2023 at Morgan Farm, Sukabanjar village, Pesawaran district, Lampung. The analysis was carried out in the animal nutrition and feed laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a randomized block design with 3 treatments and 3 replications using 9 etawa crossbreed dairy goats. The treatments used were P1 (25% casava waste forage + 75% concentrate); P2 (50% casava waste forage + 50% concentrate); and P3 (75% casava waste forage + 25% concentrate). The data obtained were analyzed for variance at a real level of 5%. The results of the analysis of variance show the ratio forage and concentrate had no significant effect (P>0.05) on dry matter consumption, dry matter and organic matter digestibility in etawa crossbreed dairy goats.